2008
DOI: 10.1108/09574090810895988
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain security: an overview and research agenda

Abstract: Purpose -Supply chain security (SCS), as a component of an organization's overall supply chain risk management strategy, has become a critical factor for businesses and government agencies since September 11, 2001, yet little empirical research supports policy or practice for the field. Therefore, this paper develops and presents a categorization of SCS based on existing research. This categorization of supply chain literature can help academics and practitioners to better understand SCS and also helps to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
121
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(125 citation statements)
references
References 50 publications
1
121
0
3
Order By: Relevance
“…Penelitian kemudian terus dikembangkan oleh Juttner [8], Khan [9], William [10], Vanany [11], Rao [12], Tang [13], Ghadge [14]. Matook [15] membuat sebuah kerangka kerja manajemen risiko terhadap pemasok yang bertujuan untuk meningkatkan proses manajemen risiko keseluruhan.…”
Section: Studi Hasil Penelitian Terdahuluunclassified
“…Penelitian kemudian terus dikembangkan oleh Juttner [8], Khan [9], William [10], Vanany [11], Rao [12], Tang [13], Ghadge [14]. Matook [15] membuat sebuah kerangka kerja manajemen risiko terhadap pemasok yang bertujuan untuk meningkatkan proses manajemen risiko keseluruhan.…”
Section: Studi Hasil Penelitian Terdahuluunclassified
“…67 % scientific articles follow this formula [9]. However, Williams [15] and Levi [7] demonstrated that "calculating risk as a probability-impact matrix to quantify and prioritize risks is misleading" [15]. [16] affirm that risk analysis need not to use probabilities because these latter may be irrelevant.…”
Section: Supply Chain Risk Methodologiesmentioning
confidence: 99%
“…Faisal et al (2007) gave a framework focusing on risk to small and medium-scale industries, while Williams et al (2008) did the same work to focus on supply chain security against terrorist activity. Autry and Bobbitt (2008) analysed a structured managerial interviews concerning supply chain security, and identified factors most related to those managers' views of supply chain security.…”
Section: Literature Reviewmentioning
confidence: 99%